2015
DOI: 10.1186/s12934-015-0279-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a bifunctional enzyme, CrtS, enhances astaxanthin synthesis through two pathways in Phaffia rhodozyma

Abstract: BackgroundA moderate-temperature, astaxanthin-overproducing mutant strain (termed MK19) of Phaffia rhodozyma was generated in our laboratory. The intracellular astaxanthin content of MK19 was 17-fold higher than that of wild-type. The TLC profile of MK19 showed a band for an unknown carotenoid pigment between those of β-carotene and astaxanthin. In the present study, we attempted to identify the unknown pigment and to enhance astaxanthin synthesis in MK19 by overexpression of the crtS gene that encodes astaxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…In the present study, β-carotene was contained in the cell extracts of all four yeasts that enhanced laccase production in co-culture, and no other carotenoids were found. The four yeasts were R. mucilaginosa (Moline et al, 2012), Phaffia rhodozyma (Shi et al, 2014; Chi et al, 2015), S. pararoseus (Han et al, 2012, 2016) and R. glutinis (Wang et al, 2008; Roadjanakamolson and Suntornsuk, 2010), and have been previously reported as β-carotene-producing strains. Therefore, microbial strains that accumulate β-carotene could be the primary agent that enhances laccase production by fungi in a co-culture.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, β-carotene was contained in the cell extracts of all four yeasts that enhanced laccase production in co-culture, and no other carotenoids were found. The four yeasts were R. mucilaginosa (Moline et al, 2012), Phaffia rhodozyma (Shi et al, 2014; Chi et al, 2015), S. pararoseus (Han et al, 2012, 2016) and R. glutinis (Wang et al, 2008; Roadjanakamolson and Suntornsuk, 2010), and have been previously reported as β-carotene-producing strains. Therefore, microbial strains that accumulate β-carotene could be the primary agent that enhances laccase production by fungi in a co-culture.…”
Section: Discussionmentioning
confidence: 96%
“…mRNA content at 28 °C for acc1(comp13834_c0), the rst key regulatory gene in f.a. synthetic pathway[26], was ~25% that at 21 °C. Low transcription of acc1 in MK19 at 28 °C accounts for the low f.a.…”
mentioning
confidence: 89%
“…mRNA content at 28 °C for acc1(comp13834_c0), the rst key regulatory gene in f.a. synthetic pathway [26], was ~25% relative to 21 °C. Low transcription of acc1 in MK19 at 28 °C accounts for the low f.a.…”
Section: Transcriptional Pro Ling Of Mk19 Under 28 °C Stressmentioning
confidence: 99%